Acts of arguing : a rhetorical model of argument - Tindale, Christopher W. (Christopher William) (SUNY series in logic and language., 1999)
"The revival of argumentation theory in the past few decades has focused on its logical and dialectical dimensions, with less attention paid to rhetorical features. This book explores and then redresses this imbalance. Tindale examines important logical and dialectical innovations in recent argumentation theory and shows that they depend implicitly upon rhetorical features of argument that have been suppressed in the account. This is illustrated using two extended case studies, one looking at Shell International's defense of its actions in Nigeria after the death of Ken Saro-Wiwa, and the other exploring the uses of character-based argument and testimony in a Holocaust-denial text and legal trial."--Jacket